2022
DOI: 10.2196/37842
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying Patients Who Meet Criteria for Genetic Testing of Hereditary Cancers Based on Structured and Unstructured Family Health History Data in the Electronic Health Record: Natural Language Processing Approach

Abstract: Background Family health history has been recognized as an essential factor for cancer risk assessment and is an integral part of many cancer screening guidelines, including genetic testing for personalized clinical management strategies. However, manually identifying eligible candidates for genetic testing is labor intensive. Objective The aim of this study was to develop a natural language processing (NLP) pipeline and assess its contribution to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In the future, incorporation of existing AP imaging results using natural language processing of radiology reports to specify true pancreatic cysts could further improve the identification of these high-risk individuals. 30 In addition, while the family history would be a useful candidate predictor, it is not always 31,32 and in the future after validation of these pipelines, we could include family history along with germline genetic risk for PC 33 as candidate predictors, as has previously been performed for other cancers. 34 Furthermore, we could also focus our risk prediction model solely on pancreatic ductal adenocarcinoma, although this already composes 90% of all PC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the future, incorporation of existing AP imaging results using natural language processing of radiology reports to specify true pancreatic cysts could further improve the identification of these high-risk individuals. 30 In addition, while the family history would be a useful candidate predictor, it is not always 31,32 and in the future after validation of these pipelines, we could include family history along with germline genetic risk for PC 33 as candidate predictors, as has previously been performed for other cancers. 34 Furthermore, we could also focus our risk prediction model solely on pancreatic ductal adenocarcinoma, although this already composes 90% of all PC.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, while the family history would be a useful candidate predictor, it is not always available nor easily accessible in a structured format. Natural language processing has been tested in other electronic health record systems to create structured values for family history, 31,32 and in the future after validation of these pipelines, we could include family history along with germline genetic risk for PC 33 as candidate predictors, as has previously been performed for other cancers 34 . Furthermore, we could also focus our risk prediction model solely on pancreatic ductal adenocarcinoma, although this already composes 90% of all PC 30 …”
Section: Discussionmentioning
confidence: 99%
“…Details of the development and evaluation of the SD + NLP algorithm are described elsewhere. [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…A variety of such solutions have arisen in recent years. [27][28][29][30][31] This includes automated algorithms that leverage family history information already captured in the EHR 31 as well as patient-facing digital tools that perform hereditary cancer risk assessment based on patient-entered personal and family history. 27,28,30 Studies have found that such digital tools effectively identify at-risk patients who would have been overlooked.…”
Section: Introductionmentioning
confidence: 99%